2013
DOI: 10.33225/jbse/13.12.592
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 5e Learning Cycle on Mental Ability of Elementary Students

Abstract: The purpose of this research is to investigate effect of 5E learning cycle instruction on 4th grade students’ mental ability in the unit of “Introduction to the Matter”. The subjects of this study were 160 students from four different classes enrolled to Science Course in an Elementary School in TURKEY. Non-equivalent pre-test/post-test control group design was used. Two of the classes randomly chosen as experimental group (79) took 5E learning cycle instruction, and the other two chosen as control group (81),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…As a result, overall, students expressed positive opinions despite some negative opinions. According to the literature, generally, students have expressed positive opinions on the learning environment prepared with the 5E learning model (Bilgin et al, 2013;Demirbas & Pektas, 2015;Metin et al, 2011). Evans (2004) stated that the 5E learning model supports the students actively participating in the class, taking responsibility, and enjoying it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, overall, students expressed positive opinions despite some negative opinions. According to the literature, generally, students have expressed positive opinions on the learning environment prepared with the 5E learning model (Bilgin et al, 2013;Demirbas & Pektas, 2015;Metin et al, 2011). Evans (2004) stated that the 5E learning model supports the students actively participating in the class, taking responsibility, and enjoying it.…”
Section: Discussionmentioning
confidence: 99%
“…The 5E learning model is one of the learning models that provides the possibility to use different methods and techniques in a class environment, is identified with the constructivist learning approach and can be used efficiently in science education (Hun, 2017). There are studies in the literature that have shown that the 5E learning model improves students' attitudes, success, motivation, meaningful learning, and conceptual understanding (Aktas, 2013;Bilgin et al, 2013;Campbell, 2006;Ceylan & Geban, 2009;Putra et al, 2018;Qarareh, 2012;Yalcin & Bayrakceken, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ketiga aktivitas tersebut terintegrasi dalam tahap LC 5E, sehingga LKPD yang dikembangkan mampu membantu peserta didik untuk memahami materi lumut. Hal tersebut sesuai penelitian Bilgin, et al, (2013) bahwa pembelajaran LC 5E memperoleh hasil yang tinggi dalam penguasaan konsep.…”
Section: Respons Guru Terhadap Lkpd Lumutunclassified